(3GJNGP GdbQGQGJ GdUYHI HGSJNOGe eLehYI fXe HQGeL COhGJ GdbQGQ (B:s (3GdcJGH GdGhd (B/s - (3cdjeGf, QhHQJs; (3SQhQ, SQhQ Ydj GHQGgje s ((3GdQjGV(B: s (3OGQ GdeQjN(B, s, 2010)
(3ebOeI dJMdjd GdbQGQ JJfGhd GdYKI GdZLQjI hhRGQI GdRQGYI HhdGjI ChQjLhf GdGeQjcjI HGdJWQb Gdi deGPG Jchf GdbQGQGJ GdUYHI h deGPG jOQS JMdjd GdbQGQ (B... (3, (B1) (3fePLI GdbQGQGJ (B: (3YfGUQ eTGcd GdbQGQGJ , gjcdI GdbQGQGJ , Yed GdGNJjGQGJ , JMdjd GdMSGSjI , GdGHOGY h gjcdI GdbQGQ (B2) (3fePLI YOe GdJCcO (B: (3CSGSjGJ GdGMJeGdGJ , GdGMJeGd GdTNUj (B.s
Keywords: (3EJNGP GdbQGQs; (3GdGLQGAGJ GdGOGQjIs; (3GdbQGQGJ GdGOGQjIs